Patenting of Intellectual Properties in Cyotherapy at the State Institution ’Scientifi c-Practical Medical Rehabilitation and Diagnostic Center of the Ministry of Health of Ukraine’ - Humenyuk, Vadym V.; Serdyuk, Irina A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 185.